Peranan Bpjs Ketenagakerjaan Dalam Pelaksanaan Program Jaminan Kecelakaan Kerja (JKK) Bagi Mitra Ojek Online - Anita Kartika Dewi; Cyndi Yuniarti; Sigit Santoso (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2023)
Abstract.The aim of this research is to analyze the implementation of the Social Security Administering Agency for work accidents experienced by workers and the implementation of the Social Security Administering Agency for work accidents experienced by workers. This research uses descriptive analytical research with a normative juridical approach. The results of this research show that BPJS Employment protects online motorcycle taxi partners with its five programs, namely; work accident insurance, old age insurance, death insurance, pension insurance and job loss insurance. The obstacle in employment protection for online motorcycle taxi partners is that there are still several online motorcycle taxi partners who are not registered as BPJS Employment participants due to various reasons, which means that protection for online motorcycle taxi partners is still not optimal.